ANALISIS SIKLUS TEORI PEMBERLAKUAN HUKUM ISLAM PADA PENGUATAN REGULASI HUKUM EKONOMI SYARIAH - Fadliah Mubakkirah; Dwi Utami Hudaya Nur; Ahmad Arief (Tadayun: Jurnal Hukum Ekonomi Syariah, 2022)
This study examines the theories of the application of Islamic law that were born from the thoughts of Islamic law experts, namely the theory of receptie exit, existence, and eclecticism. The presence of theories from Islamic law thinkers is an illustration of the cycle of legal thought in Indonesia, which started from the independence of Indonesia. Interestingly, there is no correlation between the application of Islamic law in all aspects, especially in the field of economic law. The discussion of the field of economic law only began to develop in the 1990s, followed by the issuance of regulations related to Islamic economics. Seeing this phenomenon, the research question in this paper was "how is the relationship between strengthening sharia economic law regulations with the theory of Islamic law enforcement based on cycle analysis?". The method used in this paper was a literature study with Ibn Khaldun's cyclical approach. Based on the analysis of the cycle theory, the theory of the application of Islamic law is divided into two phases, namely badawah and hadarah. Receptie exit and existence theories are classified as badawah phase. In the badawah phase there has not been a single discussion of the legal aspects of sharia economics. The strengthening of sharia economic law has just published its regulations in the hadarah phase. Abstrak Penelitian ini mengkaji tentang teori-teori pemberlakuan hukum Islam yang lahir dari pemikiran para pakar hukum Islam yaitu teori receptie exit, eksistensi, eklektisisme. Kehadiran teori dari para pemikir hukum Islam merupakan gambaran siklus pemikiran hukum di Indonesia yang titik awalnya dimulai sejak kemerdekaan Indonesia. Menariknya tidak terdapat korelasi pemberlakuan hukum Islam pada seluruh aspek khususnya bidang hukum ekonomi, pembahasan bidang hukum ekonomi baru mulai berkembang pada tahun 1990an, diikuti dengan terbitnya regulasi-regulasi yang berkaitan ekonomi syariah. Melihat fenomena tersebut maka pertanyaan penelitian pada tulisan ini adalah “bagaimana hubungan penguatan regulasi hukum ekonomi syariah dengan teori pemberlakuan hukum Islam berdasarkan analisis siklus?”. Metode yang digunakan dalam tulisan ini adalah studi kepustakaan dengan pendekatan siklus Ibnu Khaldun sebagai metode analisisnya. Berdasarkan analisis teori siklus, maka teori pemberlakuan hukum Islam dibagi menjadi dua fase yaitu badawah dan hadarah, teori receptie exit dan eksistensi diklasifikasi sebaga fase badawah, pada fase badawah belum ada satupun pembahasan aspek hukum ekonomi syariah, penguatan hukum ekonomi syariah baru terbit regulasinya pada fase hadarah.